2016
DOI: 10.1371/journal.pone.0161126
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction and Relationships with Insomnia, Anxiety, Depression, Stress and Self-Esteem in University Students: A Cross-Sectional Designed Study

Abstract: Background and AimsInternet addiction (IA) could be a major concern in university medical students aiming to develop into health professionals. The implications of this addiction as well as its association with sleep, mood disorders and self-esteem can hinder their studies, impact their long-term career goals and have wide and detrimental consequences for society as a whole. The objectives of this study were to: 1) Assess potential IA in university medical students, as well as factors associated with it; 2) As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
297
17
30

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(393 citation statements)
references
References 58 publications
49
297
17
30
Order By: Relevance
“…The results indicate that there is a significant relationship between Internet addiction and academic burnout. The results of Mohammad Beigi and colleagues showed that the dependence on the Internet is associated with failing an exam, number of units spent, and low average in recent terms significantly, therefore, it leads to students' academic failure, which was consistent with our study (2). Beard quoted by Moiedfar concluded that the use of Internet, until late, from universities causes the dangers of inappropriate use of the Internet and the problems in the curriculum of academic, this was consistent with our study (39).…”
Section: Discussionsupporting
confidence: 92%
“…The results indicate that there is a significant relationship between Internet addiction and academic burnout. The results of Mohammad Beigi and colleagues showed that the dependence on the Internet is associated with failing an exam, number of units spent, and low average in recent terms significantly, therefore, it leads to students' academic failure, which was consistent with our study (2). Beard quoted by Moiedfar concluded that the use of Internet, until late, from universities causes the dangers of inappropriate use of the Internet and the problems in the curriculum of academic, this was consistent with our study (39).…”
Section: Discussionsupporting
confidence: 92%
“…Diferentes investigações chegam à conclusão de que a AI, muitas vezes, está relacionada a transtornos mentais, especialmente depressão e ansiedade 1,6,8,15 . A depressão é a doença psiquiátrica mais relatada quando associada ao uso problemático da internet em adolescentes e ao aumento de depressão em adultos 2,5,20,21 .…”
Section: Discussionunclassified
“…Adicção por internet, dependência, uso patológico, vício ou uso problemático são termos utilizados como sinônimos na literatura para nomear esse uso desadaptativo 2,6 . Esse transtorno é descrito como uma preocupação intensa com o uso da internet, uso compulsivo, gasto de tempo excessivo na web, inabilidade para manejar esse tempo, considerando ainda o mundo sem internet desinteressante, irritabilidade no caso de ser interrompido quando está conectado e diminuição dos relacionamentos sociais por causa desse uso 2,7 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…El estudio "Internet Addition and Relationships with Insomnia Anxiety, Depression, stress and Self-Esteem in University Students: a across-sectional designed study" señala que se encontró relación entre la posible adicción a internet con depresión, ansiedad y estrés 26 .…”
Section: Adicción a Internetunclassified